2018
DOI: 10.1016/j.eclinm.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 23-Valent Polysaccharide Pneumococcal Vaccine and Changes in Invasive Pneumococcal Disease Incidence from 2000 to 2017 in Those Aged 65 and Over in England and Wales

Abstract: Background Invasive Pneumococcal Disease (IPD) is a major public health concern. The effectiveness of 23-valent polysaccharide pneumococcal vaccine (PPV23) against IPD in older age-groups is not fully understood. We measured PPV23 effectiveness against IPD and interpreted changes in IPD incidence between 2000 and 2017. Methods Public Health England conducts enhanced national IPD surveillance in England and Wales. The indirect cohort method was used to estimate PPV23 eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 10 publications
4
124
2
Order By: Relevance
“…The authors found reduced VE of PPV23 by time since vaccination, with only the first two years since vaccination having a statistically significant VE (Table S3). The UK IPD surveillance study also reported a lower VE point estimate for PPV23 as the time since vaccination increased [22]. However, although the point estimate decreased from 41% for those vaccinated within two years to 23% for those vaccinated more than five years ago, the VE against VT-IPD remained statistically significant also after five years (Table S3).…”
Section: Evidence Base For Ppv23mentioning
confidence: 88%
See 4 more Smart Citations
“…The authors found reduced VE of PPV23 by time since vaccination, with only the first two years since vaccination having a statistically significant VE (Table S3). The UK IPD surveillance study also reported a lower VE point estimate for PPV23 as the time since vaccination increased [22]. However, although the point estimate decreased from 41% for those vaccinated within two years to 23% for those vaccinated more than five years ago, the VE against VT-IPD remained statistically significant also after five years (Table S3).…”
Section: Evidence Base For Ppv23mentioning
confidence: 88%
“…For PPV23 we identified one cohort study from Germany [20], one TND study from Japan [21], one indirect cohort study from United Kingdom (UK) [22] and three case-control studies from Spain [23], Japan [24] and South Korea [25], respectively ( Table 1). The German cohort study included almost 739,000 inhabitants aged ≥60 years, retrospectively, using routine insurance data collected between 2010 and 2011.…”
Section: Polysaccharide Vaccinementioning
confidence: 99%
See 3 more Smart Citations